Self-repairing super-long-cycle low-temperature magnesium electrolyte, preparation method and application
By using magnesium chloride and dibutyl boron trifluoromethanesulfonate in the magnesium ion battery electrolyte for in-situ one-pot reaction, a self-healing ultra-long cycle low-temperature magnesium electrolyte was prepared, which solved the problem of short cycle life of the existing electrolyte under low temperature conditions and achieved efficient and stable performance of magnesium ion battery.
Patent Information
- Application Number
- CN202510116419.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing magnesium ion battery electrolytes have problems such as large overpotential, low deposition and dissolution efficiency, and short cycle life, especially in low temperature conditions.
By dissolving magnesium chloride and dibutyl boron trifluoromethanesulfonate in an organic solvent, an in-situ Lewis acid-base reaction was carried out to prepare a self-healing ultra-long cycle low-temperature magnesium electrolyte. The electrolyte can self-heal at the interface of the negative magnesium electrode, forming a SEI interface layer rich in B-O and F, and improving the circulation stability of the electrolyte.
The ultra-long cycle stability of magnesium ion batteries is achieved, and the stable cycle can be maintained especially under high current density and low temperature -30°C conditions, showing high Coulombic efficiency and low overpotential, and the electrolyte can also withstand high current density.
Smart Images

Figure CN119890440A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rechargeable magnesium batteries, and in particular to a self-repairing ultra-long cycle low-temperature magnesium electrolyte, a preparation method and an application thereof. Background Art
[0002] In metal rechargeable batteries, magnesium metal is cheap, safe, abundant in the earth's crust, and has a high volumetric capacity (3833 mAh cm -3 ) and low reduction potential (-2.37V vs. standard hydrogen electrode, SHE), it is possible to replace the lithium negative electrode. However, the performance of existing electrolytes still hinders the commercial development of magnesium-ion batteries, and there are a series of problems that need to be solved, such as passivation film, low coulombic efficiency, large overpotential, poor stability, etc. According to the properties of the material, magnesium-ion battery electrolytes are mainly divided into two categories, one is nucleophilic electrolytes and the other is non-nucleophilic electrolytes. Nucleophilic electrolytes are mainly Grignard reagent-type electrolytes, such as DCC and phenylmagnesium chloride-aluminum chloride electrolytes (APC). APC electrolyte is still one of the mainstream electrolytes with high reversibility and high cyclic stability in magnesium-ion battery research, but the nucleophilicity of APC hinders its application in Mg-S batteries. At the same time, the solvation effect of APC electrolyte is large, and it is difficult for magnesium ions to be inserted / removed in many positive electrode materials, and there is even no embedding specific capacity. The non-nucleophilic electrolytes mainly include magnesium aluminum chloride complex (MACC), hexamethyldisilazane magnesium (HMDS)-based electrolytes, boron-based magnesium electrolytes and Mg(TFSI)2-based electrolytes. The magnesium-aluminum-chloride complex MACC electrolyte can achieve reversible magnesium deposition / dissolution and has a wide electrochemical window (3.25V), but it is highly corrosive to the current collector and has poor cycle stability. The HMDS-based electrolyte has a narrow electrochemical window and low conductivity. When pure HMDSMgCl uses THF as a solvent, the electrochemical window is only 2.4V (on Pt), and the HMDS-based electrolyte is expensive (1760 yuan / 5g). Mg(TFSI)2 is very sensitive to moisture and oxygen and can easily passivate the magnesium negative electrode interface. Boron-based magnesium electrolytes include Mg[B(Ohfip)4]2 / DME, Mg(BBu2Ph2)2 / THF, Mg(CB 11 H 12 )2 / TG and other electrolytes. Mg[B(Ohfip)4]2 is considered to be an ideal magnesium ion battery electrolyte among existing boron-based electrolytes, with an electrochemical window of 4.5V and an ionic conductivity of 11mS cm -1 , but the price is expensive and the preparation process is complicated. The electrochemical window of Mg(BBu2Ph2)2 / THF is only 2.0 (on Pt), while Mg(CB 11 H 12)2 / TG electrochemical window can reach 3.8V (on Pt), which can match the high voltage window of the positive electrode material manganese dioxide. The assembled full battery has problems such as unsatisfactory cycle performance and capacity attenuation. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a self-repairing ultra-long cycle low-temperature magnesium electrolyte, a preparation method and an application. The present invention utilizes the characteristics of magnesium salts and synthesizes a new low-temperature magnesium-based electrolyte based on Lewis acid-base reaction. The electrolyte has the advantages of simple preparation process, low cost, high current tolerance, long cycle life and high Coulomb efficiency, so as to solve the problems of large overpotential, low deposition and dissolution efficiency and short cycle life of the electrolyte in the prior art.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0005] A self-repairing ultra-long cycle low-temperature magnesium electrolyte, the electrolyte comprising an organic boron-based reagent, a magnesium salt and an organic solvent; wherein the magnesium salt is magnesium chloride; the organic boron-based reagent is dibutylboron trifluoromethanesulfonate; the organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran; in the organic solvent, the concentration of magnesium chloride is 0.1 mol / L to 0.4 mol / L, and the concentration of dibutylboron trifluoromethanesulfonate is 0.2 mol / L to 0.8 mol / L.
[0006] The present invention provides a method for preparing a self-repairing ultra-long cycle low-temperature magnesium electrolyte. The specific steps for preparing the electrolyte are as follows:
[0007] Step 1: dissolving a magnesium salt in an organic solvent, and stirring and mixing at room temperature to obtain a mixed solution;
[0008] Step 2: adding an organic boron-based reagent to the mixed solution obtained in step 1, mixing and stirring to obtain the electrolyte;
[0009] The magnesium salt is magnesium chloride; the organic boron-based reagent is dibutylboron trifluoromethanesulfonate; the organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran; in the organic solvent, the concentration of magnesium chloride is 0.1 mol / L to 0.4 mol / L, and the concentration of dibutylboron trifluoromethanesulfonate is 0.2 mol / L to 0.8 mol / L.
[0010] Preferably, the preparation method is carried out under an inert gas atmosphere.
[0011] Preferably, in the mixed system of step 1 and step 2, the water content and the oxygen content are both less than 0.01 ppm.
[0012] Preferably, the magnesium salt is pretreated as follows:
[0013] The magnesium salt is vacuum dried at 70° C. to 90° C. for at least 24 hours and then sealed and stored.
[0014] Preferably, the organic solvent is pretreated as follows:
[0015] The molecular sieve is heated to 300° C. to 400° C. and activated for 4 to 6 hours, then added into the organic solvent and then sealed for storage.
[0016] The present invention provides an application of a self-repairing ultra-long cycle low-temperature magnesium electrolyte. The electrolyte or the electrolyte prepared by the preparation method is used to prepare a rechargeable magnesium ion battery.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. Aiming at the problem that the surface of magnesium negative electrode is very easy to form a passivation film in the prior art, the present invention designs and prepares the electrolyte, and obtains a new low-temperature magnesium ion battery electrolyte by an in-situ one-pot Lewis acid-base reaction of magnesium salt and organic boron-based salt. The electrolyte can self-repair the interface of magnesium negative electrode, reconstruct the SEI interface layer rich in BO and F with alternating organic and inorganic arrangements, and make the electrolyte have ultra-long cycle stability; even when the electrolyte is exposed to air, the magnesium negative electrode interface can quickly self-repair to form a stable interface, so that the magnesium ion battery still has excellent cyclability, especially at high current density, it can still maintain stable cyclability, showing considerable rate performance, and can also cope with the harsh working conditions of low temperature -30℃.
[0019] 2. The electrolyte of the present invention is at a current density of 0.5 mA / cm 2 and 0.25mAh / cm 2 Under the same conditions, the Mg||Mg symmetric battery can achieve an ultra-long cycle of 3500 hours, and the Mg||SS asymmetric battery can stably cycle for 1900 hours, showing high Coulombic efficiency (>99.5%) and low overpotential (<150mV), and the electrolyte can also withstand 6mA / cm 2 The high current density of Mg||Mg symmetric battery, after the electrolyte is exposed to air, the magnesium negative electrode can quickly self-repair to form a stable interface and can still stably cycle for 450 hours. At the same time, it can also cycle for 100 hours even at a low temperature of -30°C. The Mg||Mo6S8 full battery can stably cycle 4500 times at a high current density of 3C, and the discharge specific capacity is still 50mAh g -1 .
[0020] 3. The electrolyte of the present invention can be prepared by a one-pot method without the need to use additives such as ionic liquids with higher costs or to add multiple additives and adjust the proportions, thereby avoiding disadvantages such as high viscosity and high cost. At the same time, the preparation process of the electrolyte of the present invention is simple, the preparation and synthesis time is short, and the reaction conditions are mild. No toxic gas is generated during the reaction, which meets the requirements of green environmental protection and is therefore easy to use for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a graph of cycle number-Coulomb efficiency of the Mg||SS asymmetric battery of Example 1 of the present invention and the comparative example.
[0022] Figure 2 Linear scanning voltammograms of the electrolyte prepared in Example 1 of the present invention on different working electrodes.
[0023] Figure 3 This is a long cycle performance diagram of the Mg||Mg symmetric battery of the electrolyte prepared in Example 1 of the present invention.
[0024] Figure 4 This is a diagram of the cycle performance of a Mg||Mg symmetric battery with the electrolyte prepared in Example 1 of the present invention at low temperature.
[0025] Figure 5 This is a graph of the long-cycle performance in air of a Mg||Mg symmetric battery of the electrolyte prepared in Example 1 of the present invention.
[0026] Figure 6 This is a long cycle performance diagram of the electrolyte Mg||Mo6S8 full battery prepared in Example 1 of the present invention at a high current of 3C. DETAILED DESCRIPTION
[0027] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0028] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0029] 1. A self-repairing ultra-long cycle low-temperature magnesium electrolyte
[0030] The electrolyte of the present invention comprises an organic boron-based reagent, a magnesium salt and an organic solvent; wherein the magnesium salt is magnesium chloride; the organic boron-based reagent is dibutylboron trifluoromethanesulfonate; the organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran; in the organic solvent, the concentration of magnesium chloride is 0.1 mol / L to 0.4 mol / L, and the concentration of dibutylboron trifluoromethanesulfonate is 0.2 mol / L to 0.8 mol / L.
[0031] After in-depth research on the technical problems existing in the prior art, the present invention found that both the magnesium-aluminum-chloride complex MACC electrolyte and the APC electrolyte have the problems of large overpotential, low deposition and dissolution efficiency, and short cycle life. For this reason, the present invention conceives to improve the components of the electrolyte in the hope of improving the cycle stability of the electrolyte. When studying magnesium salts, the present invention found that some magnesium salts and some organic boron-based reagents can react in situ to obtain a new type of low-temperature electrolyte. The electrolyte can self-repair the magnesium negative electrode interface, reconstruct the organic-inorganic alternating arrangement and rich in BO and F SEI interface layering, so that the electrolyte has ultra-long cycle stability; even when the electrolyte is exposed to air, the magnesium negative electrode interface can quickly self-repair to form a stable interface, so that the magnesium ion battery still has excellent cyclicity, especially at high current density. It can still maintain stable cyclicity, showing considerable rate performance, and can also cope with the harsh working conditions of low temperature -30°C.
[0032] In some embodiments of the present invention, the magnesium salt is magnesium chloride. The organic boron-based reagent is dibutyl boron trifluoromethanesulfonate. The organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran. As a simple inorganic magnesium salt, magnesium chloride MgCl2 is a potential raw material for magnesium ion battery electrolyte and a common component of reported magnesium electrolytes. It has the advantages of low cost, abundant resources, and easy availability. Chloride ions have a high Lewis alkalinity and can effectively reduce the strong solvation effect; chlorine-containing complexes can be preferentially adsorbed on the surface of the metal magnesium negative electrode to inhibit the formation of magnesium passivation film. However, MgCl2 has extremely low solubility in more organic solvents, such as pure magnesium chloride in ethylene glycol dimethyl ether (DME) as low as 0.02M, so the pure magnesium chloride electrolyte system cannot work properly in magnesium ion batteries. Therefore, the present invention combines the advantages of magnesium chloride and boron-based electrolytes to develop a new type of magnesium chloride system boron-based electrolyte for magnesium ion batteries. The reason for selecting these two magnesium salts and organic boron-based reagents is that the present invention found that after reacting with Lewis acid trifluoromethanesulfonic acid dibutylboron, a new active anion B (CF3SO3) was formed. 4-This kind of active anion has a higher HOMO and a lower LUMO energy level. It preferentially decomposes to form a SEI layer containing BO and F during the cycle, which promotes the cycle stability of the battery, thereby achieving self-repair of the magnesium negative electrode interface, tolerance to low temperatures of -30°C, and ultra-long cycle stability. However, if other magnesium salts and organic boron-based reagents are selected, the above effects will not occur at all, for example, magnesium trifluoromethanesulfonate, magnesium fluoride, magnesium ethoxide or magnesium nitride; as well as tetrahydroxydiborane or dimethylaminoborane, these magnesium salts and organic boron-based reagents cannot achieve the above effects at all.
[0033] In some embodiments of the present invention, in an organic solvent, the concentration of the magnesium salt is 0.1mol / L to 0.4mol / L, and the concentration of the organic boron-based reagent is 0.2mol / L to 0.8mol / L. If the concentration of the magnesium salt is higher than this range, the migration number of ions in the electrolyte will be reduced, and the ion transmission resistance will be increased. If the concentration is lower than this range, the system ion conductivity will be low, the ion transmission capacity will be poor, and the internal resistance of the battery will be significantly increased. Therefore, in an organic solvent, the concentration of the magnesium salt can be 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, etc., as well as all ranges and sub-ranges between the above values. A concentration of the organic boron-based reagent higher than this range will lead to increased corrosiveness of the body, corroding the magnesium negative electrode interface, which will lead to a decrease in the stability of the magnesium ion battery; and a concentration lower than this range will cause it to react insufficiently with the magnesium salt, resulting in some magnesium salts being insoluble. Therefore, in an organic solvent, the concentration of the organoboron-based reagent can be 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0034] 2. A method for preparing a self-repairing ultra-long cycle low-temperature magnesium electrolyte
[0035] Step 1: dissolving a magnesium salt in an organic solvent, and stirring and mixing at room temperature to obtain a mixed solution;
[0036] Step 2: adding an organic boron-based reagent to the mixed solution obtained in step 1, mixing and stirring to obtain the electrolyte;
[0037] The magnesium salt is magnesium chloride; the organic boron-based reagent is dibutylboron trifluoromethanesulfonate; the organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran; in the organic solvent, the concentration of the magnesium salt is 0.1 mol / L to 0.4 mol / L, and the concentration of the organic boron-based reagent is 0.2 mol / L to 0.8 mol / L.
[0038] In some embodiments of the present invention, the preparation method is carried out under an inert gas atmosphere. Under the protection of the inert gas atmosphere, oxygen can be prevented from entering the electrolyte, thereby protecting the magnesium negative electrode from oxidation and also protecting the stability of the electrolyte.
[0039] In some embodiments of the present invention, in the mixed system of step 1 and step 2, the water content and the oxygen content are both less than 0.01 ppm, thereby eliminating the side reaction of water and oxygen in the system and reducing the generation of by-products.
[0040] In some embodiments of the present invention, the magnesium salt is pretreated as follows:
[0041] The magnesium salt is vacuum dried at 70° C. to 90° C. for at least 24 hours and then sealed and stored to remove water and oxygen in the magnesium salt.
[0042] In some embodiments of the present invention, the organic solvent is pretreated as follows:
[0043] The molecular sieve is heated to 300° C. to 400° C. and activated for 4 to 6 hours, then added to the organic solvent and sealed for storage. Water and oxygen in the solvent are removed.
[0044] 3. Application of a self-repairing ultra-long cycle low-temperature magnesium electrolyte
[0045] The electrolyte of the present invention or the electrolyte prepared by the preparation method is used to prepare a rechargeable magnesium ion battery.
[0046] 4. Examples and Comparative Examples
[0047] Example 1
[0048] Step 1 Solvent pretreatment: Add the organic solvent ethylene glycol dimethyl ether while it is hot and activated at 300℃ for 5 hours Molecular sieves should be sealed and stored in a glove box.
[0049] Step 2: Pretreatment of magnesium salt electrolyte: After the magnesium chloride is vacuum dried at 80° C. for 24 hours, it is placed in a sealed glove box for storage.
[0050] Step 3 Preparation of electrolyte: All reactions were carried out under an inert atmosphere without water or oxygen. Take 1.25 ml of ethylene glycol dimethyl ether, slowly add 0.0238 g of magnesium chloride in two equal portions, and stir for 10 minutes; then add 108 μl of dibutylboron trifluoromethanesulfonate under stirring, and stir for 24 hours to obtain the electrolyte.
[0051] Example 2
[0052] An improvement was made on the basis of Example 1, except that the concentration of magnesium chloride in the organic solvent was 0.1 mol / L. The other steps were exactly the same as those in Example 1.
[0053] Example 3
[0054] An improvement was made on the basis of Example 1, except that the concentration of magnesium chloride in the organic solvent was 0.4 mol / L. The other steps were exactly the same as those in Example 1.
[0055] Example 4
[0056] An improvement was made on the basis of Example 1, except that the concentration of dibutylboron trifluoromethanesulfonate in the organic solvent was 0.2 mol / L. The other steps were exactly the same as those in Example 1.
[0057] Example 5
[0058] An improvement was made on the basis of Example 1, except that the concentration of dibutylboron trifluoromethanesulfonate in the organic solvent was 0.8 mol / L. The other steps were exactly the same as those in Example 1.
[0059] Comparative Example 1
[0060] The improvement was made on the basis of Example 1, except that: the magnesium salt was 0.0441 g of magnesium trifluoromethanesulfonate, and the concentration of the magnesium salt in the organic solvent was 0.2 mol / L. The other steps were exactly the same as those in Example 1.
[0061] Comparative Example 2
[0062] An improvement was made on the basis of Example 1, except that: the magnesium salt was 0.0156 g of magnesium fluoride, and the concentration of the magnesium salt in the organic solvent was 0.2 mol / L. The other steps were exactly the same as those in Example 1.
[0063] Comparative Example 3
[0064] An improvement was made on the basis of Example 1, except that the magnesium salt was 0.0156 g of magnesium ethoxide, and the concentration of the magnesium salt in the organic solvent was 0.2 mol / L. The other steps were exactly the same as those in Example 1.
[0065] Comparative Example 4
[0066] An improvement was made on the basis of Example 1, except that the magnesium salt was 0.0252 g of magnesium nitride, and the concentration of the magnesium salt in the organic solvent was 0.2 mol / L. The other steps were exactly the same as those in Example 1.
[0067] 5. Performance Comparison
[0068] (1) Magnesium reversible deposition / dissolution performance coulombic efficiency test:
[0069] The reversible deposition / dissolution performance of the electrolyte and the coulombic efficiency were tested by constant current charge and discharge (CP). The test was performed by assembling a CR2032 button cell, where the positive current collector was stainless steel (SS), the negative electrode was a magnesium sheet, and the separator was a glass fiber membrane (GF / A). The charging cut-off voltage was 2V and the current density was 0.1mA / cm 2 .
[0070] Taking Example 1 as an example, the results obtained by the above test method are as follows:
[0071] Example 1 The electrolyte is at 0.1 mA / cm 2 The average deposition / stripping efficiency after 200 cycles at a current density of 1.54 Å was 99%, and the deposition / stripping overpotential was 216 mV.
[0072] The electrochemical performances of the comparative examples and Example 1 are shown in the following table. 2 The average deposition / stripping efficiency after 200 cycles at a current density of 0.1 mA / cm2 was less than 90%, and the coulombic efficiency was gradually decreasing after 100 cycles, which indicates that the electrolytes of Comparative Examples 1 to 4 may be seriously passivated or decomposed, and the deposition / stripping overpotential is relatively large. 2 The average deposition / stripping efficiency after 200 cycles at a current density of is 99%. The deposition / stripping overpotential is 216 mV. Figure 1 shown.
[0073] Table 1
[0074] Performance Project Deposition stripping overpotential Coulomb efficiency Example 1 216mV 99% Comparative Example 1 399mV 85% Comparative Example 2 524mV 90% Comparative Example 3 891mV 79% Comparative Example 4 393mV 82%
[0075] It can be seen that the performance of Example 1 is better than that of the comparative example in all aspects.
[0076] (2) Magnesium deposition / dissolution oxidation stability test
[0077] The electrolyte prepared in Example 1 was tested for magnesium reversible deposition / stripping coulombic efficiency and oxidation stability by cyclic voltammetry (CV) and linear voltammetry (LSV) respectively. The test was performed by assembling CR2032 button cells, in which the positive electrode current collector was stainless steel (SS), the negative electrode was a magnesium sheet, and the separator was a glass fiber membrane. The voltage range of the linear voltammetry LSV was open circuit voltage ~ 5.0V, and the scan rate was 25mV / s.
[0078] The electrochemical stable potentials of the electrolyte prepared in Example 1 on stainless steel (SS), molybdenum foil (Mo), aluminum foil (C / Al) and copper foil (Cu) were 2.86 V, 2.55 V, 2.30 V and 2.21 V, respectively. Figure 2 As shown, vs.Mg / Mg 2+ .
[0079] (3) Magnesium reversible deposition / dissolution performance test
[0080] The reversible deposition / dissolution performance and coulombic efficiency of the electrolyte prepared in Example 1 were tested by constant current charge and discharge (CP). The test was performed by assembling a CR2032 button-type symmetrical battery, in which the positive and negative electrodes were magnesium sheets and the separator was a glass fiber membrane (GF / A). The charge and discharge time of the charge and discharge test CP was 30 min, and the current density was 0.1 mA / cm 2 ~2mA / cm 2 .
[0081] The electrolyte prepared in Example 1 is used in actual applications at a current density of 0.5 mA / cm 2 Under the same conditions, the Mg||SS battery can stably cycle for 1900 hours, and achieve a high Coulombic efficiency of >99.5% and a low overpotential of <150mV. The Mg||Mg battery can stably cycle for 3500 hours. Figure 3 shown.
[0082] The electrolyte prepared in Example 1 is used in practice at 0.1 mA / cm 2 Under the condition of current density and in the low temperature environment of -10℃~-30℃, it can work stably in cycles. Figure 4 As shown, this provides a basis for magnesium-ion batteries to operate under extreme conditions.
[0083] The electrolyte prepared in Example 1 was assembled into a symmetrical battery in air at 0.1 mA / cm 2 Under the current of , after a short period of self-repair and interface formation, it can work stably for 450 hours. Figure 5 shown.
[0084] (4) Full battery charge and discharge test
[0085] The electrolyte prepared in Example 1 was subjected to full battery charge and discharge test. Constant current charge and discharge (CP) test was performed by assembling CR2032 button-type symmetrical cells, in which the positive electrode was Mo6S8, the substrate was carbon paper (CF), the negative electrode was magnesium sheet, and the separator was glass fiber membrane (GF / A). The current was 3C.
[0086] The Mg|YBTFC|Mo6S8 full battery can be stably cycled for 4500 times at a high current density of 3C, and the capacity is maintained at 50mAh / g 1 ,like Figure 6 shown.
[0087] After the above electrochemical performance tests were carried out, the performance of Examples 2 to 5 was not much different from that of Example 1. In summary, the electrolyte of the present invention has the characteristics of long cycle stability, high magnesium deposition / dissolution efficiency, and resistance to low temperature and water and oxygen.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A self-repairing ultra-long cycle low-temperature magnesium electrolyte, characterized in that: The electrolyte comprises an organic boron-based reagent, a magnesium salt and an organic solvent; Wherein, the magnesium salt is magnesium chloride; the organic boron-based reagent is dibutylboron trifluoromethanesulfonate; the organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran; In the organic solvent, the concentration of magnesium chloride is 0.1 mol / L to 0.4 mol / L, and the concentration of dibutylboron trifluoromethanesulfonate is 0.2 mol / L to 0.8 mol / L.
2. A method for preparing a self-repairing ultra-long cycle low-temperature magnesium electrolyte, characterized in that: The electrolyte according to claim 1 is prepared by the following specific steps: Step 1: dissolving a magnesium salt in an organic solvent, and stirring and mixing at room temperature to obtain a mixed solution; Step 2: adding an organic boron-based reagent to the mixed solution obtained in step 1, mixing and stirring to obtain the electrolyte; Wherein, the magnesium salt is magnesium chloride; the organic boron-based reagent is dibutylboron trifluoromethanesulfonate; the organic solvent is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and tetrahydrofuran; In the organic solvent, the concentration of magnesium chloride is 0.1 mol / L to 0.4 mol / L, and the concentration of dibutylboron trifluoromethanesulfonate is 0.2 mol / L to 0.8 mol / L.
3. The preparation method according to claim 2, characterized in that: The preparation method is carried out under an inert gas atmosphere.
4. The preparation method according to claim 2, characterized in that: In the mixed system of step 1 and step 2, the water content and the oxygen content are both less than 0.01 ppm.
5. The preparation method according to claim 2, characterized in that: The magnesium salt is pretreated as follows: The magnesium salt is vacuum dried at 70° C. to 90° C. for at least 24 hours and then sealed and stored.
6. The preparation method according to claim 2, characterized in that: The organic solvent is pretreated as follows: The molecular sieve is heated to 300° C. to 400° C. and activated for 4 to 6 hours, then added into the organic solvent and then sealed for storage.
7. Application of a self-repairing ultra-long cycle low-temperature magnesium electrolyte, characterized in that: The electrolyte described in claim 1 or the electrolyte prepared by the preparation method described in claims 2 to 6 is used to prepare a rechargeable magnesium ion battery.
Citation Information
Cited By
Magnesium secondary battery electrolyte and preparation method thereof
CN120767411A